'Wonder at What Is as It Is': Arendtian Wonder as the Occasion for Political Responsibility. Issue 53 (3rd July 2022) - Ferguson, Magnus
ABSTRACT: Although Arendt is widely cited as an early proponent of what is sometimes called "forward-looking" or "future-looking" responsibility, scholars have not dwelled at length on Arendt's claim that the experience of thaumazein – in her view, a form of wonder intermixed with horror – can serve as the impetus for taking on expansive political responsibilities. This article has two principal aims: first, to reconstruct an implicit theory of wonder from Arendt's numerous references to thaumazein, and second, to further develop an account of thaumazein as an affective, enabling condition for revising the scope of one's responsibilities. Connecting Arendtian thaumazein to contemporary scholarship on the role of wonder and emotion in politics, I argue that thaumazein is a distinctive emotion with both political and existential salience, and that it can prompt those who experience it to scrutinize and reimagine inherited conceptual and political frameworks, including moral and legal frameworks for responsibility.